Analysis of Two Lengthwise Cracks in a Viscoelastic Inhomogeneous Beam Structure - Victor Iliev RIZOV (Engineering Transactions, 2020)
The present paper considers the time-dependent fracture in a continuously inhomogeneous viscoelastic cantilever beam with two lengthwise cracks. Time-dependent analytical solutions to the strain energy release rate, which take into account the viscoelastic behaviour of the material, are derived. A rheological model with two springs and two dashpots is used for studying the viscoelastic behaviour of the beam. A stress-strain-time relationship is obtained for the case when the rheological model is loaded by stress that increases linearly with time up to a certain level and then it remains constant. The variation of the strain energy release rate with time is analysed.